Avaliação da efetividade do Laser Terapêutico e TENS na diminuição da dor em pacientes com lombalgia - Chagas Júnior, Rainier Antonio Queiroz [UNESP] (2016)
Chagas Júnior, RAQ. Evaluation of the effectiveness of Therapeutic Laser and TENS in the reduction of pain in patients with low back pain. [Thesis]. Araçatuba: São Paulo State University (Unesp), School of Dentistry; 2016. Introduction: Low back pain is often accompanied by exacerbation of pain and decreased functional capacity. Many non-pharmacological therapies such as laser and TENS are indicated for its treatment, but their effects are not fully understood, nor is the minimum number of sessions for therapeutic effect. Objective: To analyze the effect of different therapeutic modalities (laser and TENS) non-relief of chronic non-specific chronic pain by varying the number of clinical sessions. Methods: The sample consisted of 30 patients randomly selected and divided into 2 groups treated by two therapeutic modalities: G1 - laser (n = 15), G2 - TENS (n = 15). All patients were assessed before and after treatment, by the McGill Pain Questionnaire (MPQ), and Functional Capacity by the Roland Morris Questionnaire. And evaluated daily by Visual Analog Scale (EAV). By this methodology it was possible to conclude that the proposed interventions statistically reduce the short-term pain intensity in patients with low back pain, alter the perception of the pain descriptors only in the Laser Group before and after treatment; Just as they alter the reports of physical incapacity